Security as a Central Element in Law Enforcement - Balla, Zoltán (Magyar Rendészet, 2016)
Scientific studies of security are carried out by military sciences and the evolving sciences of law enforcement. The subject matter is characterized by economic, political, military and climatic factors. The government’s strategies for security are synthesized in government decisions. The future responsibility of law enforcement is to examine security.